Fabrication-Method-Dependent Excited State Dynamics in CH3NH3PbI3 Perovskite Films. Issue 1 (December 2017) - Kim, In-Sik; Jo, Cheol; Kang, Rira; Kim, Dong-Yu; Son, Seong-Jin; Hwang, In-Wook; Ko, Do-Kyeong
Abstract Understanding the excited-state dynamics in perovskite photovoltaics is necessary for progress in these materials, but changes in dynamics depending on the fabrication processes used for perovskite photoactive layers remain poorly characterised. Here we report a comparative study on femtosecond transient absorption (TA) in CH3 NH3 PbI3 perovskite films fabricated by various solution-processing methods. The grain sizes and the number of voids between grains on each film varied according to the film synthesis method. At the low excitation fluence of 0.37 μJ cm−2, fast signal drops in TA dyanmics within 1.5 ps were observed in all perovskite films, but the signal drop magnitudes differed becuase of the variations in charge migration to trap states and band gap renormalisation. For high excitation fluences, the buil-up time of the TA signal was increased by the activated hot-phonon bottleneck, while the signal decay rate was accelerated by fluence-dependent high-order charge recombination. These fluence-dependent dynamics changed for different perovskite fabrication methords, indicating that the dynamics were affected by morphological features such as grain sizes and defects.